INVESTIGATING THE CHALLENGES FACING DRAINAGE WATER REUSE STRATEGY IN EGYPT USING EMPIRICAL MODELLING AND SENSITIVITY ANALYSIS†. (11th July 2013) - Ghaffar, Eman Abdel; Shaban, M.
ABSTRACT This research investigates the challenges facing drainage water reuse (DWR) strategy in Egypt using empirical modelling and sensitivity analysis. An empirical model, that can describe the relationship between the amount of DWR in the Nile Delta and its major challenges as predictor variables, was developed. A correlation was carried out followed by multiple regression analyses. In addition, sensitivity analysis was performed to detect the most effective challenge. It was found that some of these predictors are useful for predicting DWR using a significant regression model at 0.1% level. The results revealed that fresh water released to irrigation (FWRI) is the best predictor of DWR, followed by the irrigation improvement project areas (IIP‐A) and rice cultivation area (RCA). However, it was clear that the effect of the RCA on the DWR is much stronger than the effect of IIP‐As. Meanwhile drainage water quality (DWQ) varied within a narrow range without a clear tendency where DWR showed a positive trend (continuous increase). On the other hand, the sensitivity analysis revealed that reducing fresh water released to the irrigation system by 30% will lead to a reduction in drainage water reuse up to 50%, while reducing RCAs by 30% will result in a reduction of drainage water reuse by 14.8%. Copyright © 2013 John Wiley & Sons, Ltd.